2006
DOI: 10.1542/peds.2006-0747
|View full text |Cite
|
Sign up to set email alerts
|

A Staging System for Infantile Krabbe Disease to Predict Outcome After Unrelated Umbilical Cord Blood Transplantation

Abstract: We conclude that the clinical staging system based solely on signs and symptoms of disease can be used to predict outcomes after umbilical cord blood transplantation. This staging system can be used prospectively to guide physicians unfamiliar with the disorder in evaluating, monitoring, and counseling families about treatment outcomes. The staging will be useful for both patients diagnosed with infantile Krabbe disease because of clinical symptoms and those identified through neonatal screening programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 6 publications
0
71
0
Order By: Relevance
“…Previous reports of MLD and other leukodystrophies have made recommendations to transplant patients in an early age and disease to prevent serious neurological damage. 25,[35][36][37] In patient D, MRI showed progression of white matter lesions in the period of lower enzyme levels but remained stable during further follow-up. DLI was necessary to convert mixed chimerism into complete donor chimerism, resulting in higher levels of ARSA and stabilization of cerebral progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of MLD and other leukodystrophies have made recommendations to transplant patients in an early age and disease to prevent serious neurological damage. 25,[35][36][37] In patient D, MRI showed progression of white matter lesions in the period of lower enzyme levels but remained stable during further follow-up. DLI was necessary to convert mixed chimerism into complete donor chimerism, resulting in higher levels of ARSA and stabilization of cerebral progression.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although hematopoietic stem cell transplantation performed during the first month of life may provide benefit to some infants with infantile-onset KD, 23,24,38 it is challenging for Specialty Care Centers to diagnose, evaluate, and refer infants to qualified transplant centers within the first few weeks of life. Even when transplantation is performed early, delays in development of gross motor skills have developed in most patients, including our two surviving patients.…”
Section: Original Research Articlementioning
confidence: 99%
“…21 Early studies showed that a small cohort of infantile KD patients who received umbilical cord blood transplantation from unrelated donors prior to symptom onset had preserved neurological function. [22][23][24] However, even when transplantation is performed early, delays in development of gross motor skills have developed in most patients. 22 It is critical that families be fully educated about benefits, risks, and limitations of treatment following a positive screen.…”
mentioning
confidence: 99%
“…Transplantation of umbilical cord blood in babies with infantile Krabbe's disease that favorably altered their natural history could be the first, promising example from human clinic. Infants who underwent HUCB cell graft before the development of symptoms showed progressively increasing central myelination and continued gains in developmental skills and cognitive function (Escolar et al, 2005;Escolar et al, 2007). These therapeutic benefits of cord blood infusion may hold hope for slowing the progression of other chronic neural diseases.…”
Section: The Cord Blood Challenge For Brain Repairmentioning
confidence: 99%